Cryptocurrency money laundering and artificial intelligence: a compelling tool or unethical intrusiveness? - Barisa, Anna Renāte (Riga Graduate School of Law, 2022)
Nowadays the use of cryptocurrency as a means of exchange is growing rapidly. With the technological advancements also financial crime advances, as criminals are developing new ways to launder money, finance terrorism or evade taxes. The European Union has implemented the AML/CTF Directive to combat financial crime – various procedures must be integrated within the business operations of obliged entities under the Directive. The procedures and principles are implemented with the help of Artificial Intelligence technologies. Therefore, this thesis examines and analyzes the relevant AML/CTF legislation in EU, contribution to financial crime via cryptocurrencies and how AI technology helps to integrate a risk-based approach to the legislation in financial institutions.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Money laundering; Cryptocurrency; Artificial intelligence